기체상 질소산화물을 포함한 2015-2019년도 대한민국 질소수지 연구 - 김현경(Hyun-Kyung Kim); 박성민(Seong Min Park); 박재우(Jae-Woo Park) (Daehan hwan'gyeong gonghag hoeji, 2023)
목적 : 본 논문에서는 2015년부터 2019년까지의 대한민국 질소수지를 체계적으로 이해하고, 비교 및 분석함으로써 우리나라의 연간 질소수지 경향을 파악하고자 하였다. 방법 : 질소수지는 농업 및 축산업지역, 도시지역, 임야지역으로 분류하여 산출하였다. 질소 유입은 대기로부터 침착량, 생물학적 고정량, 농업용수, 무기화학비료, 퇴비 및 사료 사용으로 인한 유입량, 생산된 농작물과 식료품 수입, 연료 사용 등에 의한 유입량을 추정하였다. 질소 유출은 탈질량, 휘발량, 지하수 유출량, 농경지 흡수량, 하수처리장 및 수계유출, 산림소비량, 질소산화물 배출량 등을 고려하여 산출하였다. 결과 및 토의 : 2015년도부터 2019년까지의 연간 총 질소수지는 6,107,449 ton/yr, 6,144,666 ton/yr, 6,245,240 ton/yr, 6,281,552 ton/yr, 5,993,347 ton/yr가 유입되었으며, 1,346,587 ton/yr, 1,369,119 ton/yr, 1,365,326 ton/yr, 1,378,941 ton/yr, 1,365,994 ton/yr가 유출되었다. 질소수지 변화에 기여도가 높은 질소산화물은 자동차, 사업장, 발전소 등에서 배출되는 질소로 모두 인간 활동이 원인이 되었으며, 매년 전체 질소수지 중 32% 이상이 질소산화물에 의한 것으로 조사되었다. 결론 : 도시화로 인한 식품 및 연료 소비량 증가로 질소수지는 2010년대에 지속적으로 증가하였다. 그러나 환경오염에 대한 인식이 점차 높아짐에 따라 배출규제와 대체재 활용 등의 노력으로 질소수지는 2019년에는 감소하였다. 따라서 질소를 효과적으로 감축하기 위해 적절한 제도의 설립과 적극적인 이행이 필요하다. Objectives : The study was aimed to systematically understand the nitrogen budget from 2015 to 2019, and to determine the annual nitrogen balance in South Korea.Methods : The nitrogen budget was calculated by classifying into agricultural and livestock, city, and forest areas. The nitrogen input was estimated from deposition, biological fixation, agricultural water, inorganic chemical fertilizer, compost, feedstuff, produced crops, imported grocery, and fuel consumption. The nitrogen output was estimated by considering denitrification, volatilization, ground water runoff, land and crop absorption, sewage disposal, drainage, forest uptake, and nitrogen oxide (NOx) emissions.Results and Discussion : The annual nitrogen budget from 2015 to 2019 showed the input as 6,107,449 ton/yr, 6,144,666 ton/yr, 6,245,240 ton/yr, 6,281,552 ton/yr, 5,993,347 ton/yr and the output as 1,346,587 ton/yr, 1,369,119 ton/yr, 1,365,327 ton/yr, 1,378,940 ton/yr, 1,365,994 ton/yr, respectively. The NOx, highly contributing to change in the nitrogen budget, was caused by human activities such as vehicles, business places, and power plants. More than 32% of the total nitrogen budget was caused by NOx in every year.Conclusion : The nitrogen budget continued to increase in the 2010s because of the increase in food and fuel consumption by urbanization. However, the nitrogen budget declined in 2019 due to the effort such as emission regulations and the use of alternatives as the awareness of environmental pollution gradually increased. Therefore, the appropriate institution should be established and actively implemented to reduce the nitrogen effectively. KCI Citation Count: 0